A new species of the genus Cerviniopsis from Sagami Bay, Japan and reinstatement of the genus Neocervinia, with a report on the male of Neocervinia itoi Lee & Yoo, 1998 (Copepoda: Harpacticoida: Aegisthidae) - Park, Eun-Ok; Shimanaga, Motohiro; Yoon, Suk Hyun; Lee, Wonchoel (Zootaxa, 2012)
A new aegisthid copepod, Cerviniopsis reducta sp. nov. is described from the deep sea in Sagami Bay, Japan. The newspecies has superficial resemblance to C. minutiseta Ito, 1983 in the armature formula of swimming legs. However theydiffer from each other in the shape of setae of the swimming legs, the distal margin of operculum, length of caudal rami,and the location of setae on P5 exopod. Also, the male of Neocervinia itoi Lee & Yoo, 1998 is described on the basis ofsamples collected from around the type locality in Sagami Bay, Japan. Sexual dimorphism of N. itoi male can be observedin the fused rostrum, atrophied mouthparts, P5, and P6. The sixth leg is symmetrical and both gonopores are presumablyactive, based on the presence of two spermatophores internally in the genital segment. This paper reports for the first timeon the sexually dimorphic characters in the genus Neocervinia Huys, Mobjerg & Kristensen, 1997, reinstating its generic status with the newly revealed male characters.